Managing Guidance and Counseling Services through Face-to-Face Media: A Case Study at SMA Negeri 1 Wanayasa - Nursyaidah, Nunung; Annisa Nur Hamidah; Salsabilah Hasana; Nadya Yulianty (JIGC (Journal of Islamic Guidance and Counseling), 2025)
Guidance and counseling services in schools play a critical role in supporting students’ academic, personal, and social development. However, the effectiveness of these services depends largely on how they are managed and delivered, particularly through appropriate media. This study aims to analyze the management of GC services through face-to-face media at SMA Negeri 1 Wanayasa, focusing on planning, implementation, supervision, and evaluation. Employing a qualitative descriptive design, data were collected through interviews with counselors, classroom observations, and documentation review, and analyzed using Miles and Huberman’s interactive model. The findings indicate that counselors employ several types of media, including counseling boards, problem boxes, leaflets, and innovative digital tools, to facilitate direct interaction with students. These media function not only as communication channels but also as management instruments that structure and expand the reach of GC services. Despite challenges such as time limitations, large student numbers, and inadequate facilities, the school’s flexible management strategies and continuous evaluation ensure that GC services remain effective. This study contributes to the literature by highlighting how face-to-face media, when strategically managed, can enhance counseling accessibility and student engagement in the Indonesian secondary school context. The findings provide practical implications for school counselors and administrators seeking to strengthen GC management, and they open avenues for comparative studies on the integration of traditional and digital media in school counseling services across diverse cultural settings